Data-Driven Implications for Translating Evidence-Based Psychotherapies into Technology-Delivered Interventions - Schroeder, Jessica; Suh, Jina; Wilks, Chelsey; Czerwinski, Mary; Munson, Sean A.; Fogarty, James; Althoff, Tim (EAI International Conference on Pervasive Computing Technologies for Healthcare, 2020)
Mobile mental health interventions have the potential to reduce barriers and increase engagement in psychotherapy. However, most current tools fail to meet evidence-based principles. In this paper, we describe data-driven design implications for translating evidence-based interventions into mobile apps. To develop these design implications, we analyzed data from a month-long field study of an app designed to support dialectical behavioral therapy, a psychotherapy that aims to teach concrete coping skills to help people better manage their mental health. We investigated whether particular skills are more or less effective in reducing distress or emotional intensity. We also characterized how an individual's disorders, characteristics, and preferences may correlate with skill effectiveness, as well as how skill-level improvements correlate with study-wide changes in depressive symptoms. We then developed a model that predicted the effectiveness of specific skills. Based on our findings, we present design implications that emphasize the importance of considering different environmental, emotional, and personal contexts. Finally, we discuss promising future opportunities for mobile apps to better support evidence-based psychotherapies, including using machine learning algorithms to develop personalized and context-aware skill recommendations.